# Completing The Square Calculator

## Now, What Exactly Is A “Completing The Square Calculator”?

A completing the square calculator is a tool that helps you find the value of a certain variable in a quadratic equation by completing the square. This process involves adding a certain term to both sides of the equation so that one side is a perfect square. This can be helpful in solving for the roots of a quadratic equation, as well as in graphing quadratic functions.

## Free Completing the Square Calculator With Steps

This is a very simple tool for Completing the Square Calculator. Follow the given process to use this tool.

☛ Step 1: Enter the complete equation/value in the input box i.e. across “Provide Required Input Value:”

☛ Step 2: Click “Enter Solve Button for Final Output”.

☛ Step 3: After that a window will appear with final output.

Hope you found this Free Completing the Square Calculator useful. Do visit usefulknot.com for more.

## Formula for completing the square

To complete the square, first find the equation of the parabola. Next, divide each term in the equation by the coefficient of x2. Finally, add 1/4 to each term in the equation.

x2 + bx + c = 0

x2 + bx = -c

1/4 (x2 + bx) = -c/4

x2 + bx + (1/4) = -c/4 + (1/4)

x2 + bx + 1/2 = -c/4

x2 + bx + 1/4 = -c/2

## Completing The Square Definition

Completing the square is a mathematical technique used to solve quadratic equations. The technique involves adding a constant to the equation so that the left side of the equation is a perfect square.

## Example of completing the square based on Formula

The standard form of a quadratic equation is given by the formula:

ax2 + bx + c = 0

where a, b, and c are coefficients.

For example, if the coefficients are a = 1, b = 2, and c = 3, then the standard form of the equation is given by 1×2 + 2x + 3 = 0.

The equation can be rewritten in the form of (x + p)2 + q = 0 by completing the square. In this case, p = -b/(2a) and q = c – b2/(4a).

Therefore, the equation can be rewritten as (x + (-2/1))2 + (3 – 4) = 0, which is equivalent to (x – 2)2 – 1 = 0.